The world of urticaria, with and without allergy - Chambel, Marta (2011)
Urticaria is a clinical entity shared by a heterogeneous group of diseases, and must be seen as a symptom and not a disease. The characteristic cutaneous lesions are erythematous papules or with a clear central zone and a peripheral erythema, pruriginous, that disappears with digital pressure and completely regresses in less than 24 hours. In some cases its accompanied by angioedema, although usually it occurs isolated. Urticaria may affect up to 25% of population in some moment of life. Acute urticaria (less than 6 weeks of duration), more frequent in children, is more prevalent than the chronic form. In cases that the etiology is identified, infections, foods and medications are the most frequent causes. Insect stings and systemic diseases are more rarely involved. In chronic urticaria, allergy IgE-mediated is rare. Complementary diagnostic exams must be criterious and supported by relevant clinical data; exhaustive analytic examinations must be avoided. Most episodes of urticaria are of short duration and spontaneous resolution. Acute urticaria has an average duration of 7 days; the chronic form has a variable evolution. Regarding the treatment, elimination of the causative agent is the ideal approach, but it isnt always possible. The first choice of symptomatic treatment are non sedative H1 antihistaminics, in higher dosage than the usually recommended. Some alternative therapeutics may be associated, but strong scientific evidence supporting their efficiency is lacking. Referral to a specialized consultation is important in some situations; some examples are allergy IgE-mediated or suspicion of systemic disease.